Red [compact disc, unabridged] - Dekker, Ted, 1962- (Dekker, Ted, 1962- Circle (Oasis Audio (Firm)), 2004)
Red picks up immediately where Black ends, and centers around the heroic attempts of Thomas Hunter to save two worlds. With the devastating realization that he has helped unleash death into both worlds, he must now discover how to defeat this evil, while trying to save his true love.